On the Endocircular Li@C16 System - Yang, Yi-Fan; Cederbaum, Lorenz S. (Frontiers in Chemistry, 2022)
The endocircular Li@C16 is a promising system as it can form both a charge-separated donor-acceptor complex and a non-charge-separated van der waals complex. By employing the state-of-the-art equation-of-motion coupled-cluster method, our study shows that the carbon ring of this system possesses high flexibility and may undertake large distortions. Due to the intricate interaction between the guest Li+ cation and the negatively charged ring, this system can form several isomers possessing different ground states. The interesting electronic structure properties indicate its applicability as a catalyst candidate in the future.